La musica nelle Chiese della Riforma. L’attualità in Italia (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Bonhoeffer, il canto nella Vita comune - 2. Il simbolo oltre le parole - 3. Emozione e razionalità - 4. Canto comunitario e decoro nella liturgia - 5. La Chiesa Luterana oggi - 6. La Chiesa Valdese e Metodista - 7. Le Chiese battiste - 8. Le Chiese pentecostali - 9. L’ambito ecumenico - 10. Alcuni esempi di canto liturgico.Music in the Churches of the Protestant Reformation, with particular attention to the current situation in ItalyABSTRACT: The concepts of new song, decorum, discipline, praise to God, community in Bonhoeffer's theology. Music as a symbolic language. The practice of community chant in Italian Protestant Churches: Lutheran Church, Waldensian and Methodist Church, Baptist Church, Pentecostal Churches. The new hymnbooks. The ecumenical circuit.